Gambaran Faktor Risiko Waktu Terapi Radiasi yang Berkepanjangan pada Pasein kanker Payudara: Studi Cross-sectional di RSUP Dr. Kariadi Tahun 2023 - Muchtar, Zahra Zetira; Adisasmita, Asri C.; Bramantyo, Dion Firli (Jurnal Epidemiologi Kesehatan Indonesia, 2025)
In Indonesia, there were more than 58,000 new breast cancer cases with nearly 23,000 deaths in 2020. Radiotherapy is one of the adjuvant therapy modalities for breast cancer. Interruptions of more than five days increase the risk of local recurrence. This study aimed to describe the risk factors associated with prolonged overall treatment time (OTT) in breast cancer patients at Dr. Kariadi General Hospital during 2023. This was a cross-sectional study using bivariate logistic regression analysis to examine the association between national holidays, deterioration of general condition, age, residence, and type of surgery prior to radiation therapy with prolonged OTT. Data were obtained from electronic medical records, and a total population sampling method was applied, resulting in 261 post-surgical breast cancer patients who met the inclusion criteria, namely newly diagnosed breast cancer patients who had undergone breast-conserving surgery (BCS) or modified radical mastectomy (MRM) followed by adjuvant radiotherapy. Patients were considered to have prolonged OTT if the interruption exceeded the number of recorded national holidays. Among the 261 patients, 21.8% (n = 57) experienced prolonged OTT. The highest proportion of prolonged OTT occurred in patients aged 50–59 years (43.9%), residing outside Semarang City/Regency (64.9%), undergoing MRM (77.2%), affected by national holidays (78.9%), and without deterioration of general condition (82.5%). Bivariate analysis showed that only national holidays and machine maintenance were statistically significantly associated with prolonged OTT (p < 0.001). As an effort to improve treatment outcomes, hospitals need to implement strategies to prevent prolonged OTT, including ensuring continuous access to radiotherapy without interruption due to machine maintenance. Keywords : Breast Cancer, Overall Treatment Time (OTT), Radiotherapy Interruption